Latin American Panel on Post Graduate Education in Agricultural Engineering - Organización de las Naciones Unidas para la Alimentación y la Agricultura (FAO) (2021)
The chapter records the sequence of events which took place during the development and proceeding of the panel. The papers presented in the panel are liged according to the themes and sequence of presentation, with the respective paper number, author, title of the work and numbrer of pages.